How Reflective Enhance Education Learning - Yaakop, Nurhidayah; Koh, Denise; Yasin, Ruhizan (CENTRAL ASIA AND THE CAUCASUS, 2022)
BACKGROUND: Reflective is an important part of learning, especially in how students understand knowledge from their peers, parents, or teachers. The results of our reflective transformation for the learning community, he community itself, and their reflective practice discuss how reflective learning and the development of one's professional identity through reflection are linked.OBJECTIVE: This study aimed to know how reflection is one of the most effective techniques to enhance learning, establish critical thinking skills among students, and explore how reflective learning can be practised in the new norm.CHALLENGES: Various studies show that reflectiveness helps their study, but the most challenging is how to adapt to the current situation in the new norm.DISCUSSIONS: Develop higher individual cognitive processes and activities focusing on identifying problems and solutions, making comparisons and contrasts, making claims and validations, and determining goals, actions, and outcomes. Reflection writing offers various advantages in the classroom, including assessing the current state of information received in a specific course and assisting students in becoming more self-reliant learners.CONCLUSION: Active, reflective practice will develop higher cognitive processes and trigger individual activity focusing on finding problems and solutions, comparisons and contrasts, statements and validations, goals, actions, and outcomes. Participants said that reflection was a highly useful tool for identifying strengths and flaws, as well as for improving and evaluating activities. It has also been noted that reflection is important in examining students' experiences and assessing themselves. Most importantly, it will assist us in correcting our own errors so that we do not repeat them in the future, especially given the new norm.